A COMPARISON OF SOME TRANSLATIONS OF GOOGLE AND THOSE OF TIM KUNCI CULTURAL STUDIES CENTER - Marjohan, Asril Marjohan; Putra Yadnya, Prof. Dr. Drs. Ida Bagus Putra Yadnya, M; Mbete, Aron Meko Mbete (e-Journal of Linguistics; Vol.7. Januari 2013 No. 1, 2013)
This study was aimed at describing Google translations by comparing them with those which were carried out by humans. The human translations used in this study were done by Tim Kunci Cultural Studies Center . This study used qualitative-descriptive method. The sample was purposively selected and consisted of 24 sentences from Chris Barker, Cultural Studies and their two translated versions. The evaluation was done by using Sical’s approach. The results showed that Google translations contained more errors than those made by Tim Kunci Cultural Studies Center. Google made errors that fell into the category of violations of linguistic and sociocultural rules or norms. This was caused by the design of Google Translate that was not based on linguistic and sociocultural analyses.  Meanwhile   Tim Kunci Cultural Studies Center made errors that indicated reasoning by guessing meanings from context, as what humans are doing in communication. Google translations needed revising in  the forms of translating words which had been left untranslated, retranslating words which had been wrongly translated because of not considering context, retranslating phrases which had been wrongly translated because of  not analyzing them into their constituents and propositions, retranslating words which had been wrongly translated because of not considering sociocultural norms. In doing the revisions the editor had to read the original text because the translations tended not to give clues to the original patterns of the sentences for their highly varied forms.   Meanwhile, the translations of Tim Kunci Cultural Studies Center needed minor editing to make them more effective. There was no need for an intensive reading of the original for their   more systematic characteristics.
Keywords: Google, human, translation